EFFECTIVE METHODS FOR IMPROVING GRAMMAR COMPETENCE IN ENGLISH LESSONS - Toshpulаtov Temur Muminjonovich (Innovate Conferences, 2025)
The article explores effective methods for improving grammar competence in English lessons, highlighting the central role of grammar in the development of communicative skills. It analyzes traditional and modern approaches to grammar teaching, emphasizing the importance of combining structural knowledge with practical application in speech. Special attention is given to learner-centered methods, including project-based learning, interactive activities, and the use of digital technologies, which enhance students’ motivation and ensure the gradual development of grammatical proficiency. The findings suggest that integrating innovative pedagogical strategies with systematic grammar instruction contributes not only to linguistic accuracy but also to the overall communicative competence of learners.
Keywords: Grammar competence, English lessons, communicative competence, teaching methods, language learning strategies, learner-centered approach, innovative technologies.